Recent findings of Ommastrephes bartramii (Cephalopoda: Ommastrephidae) in the eastern Mediterranean and the implication on its range expansion - LEFKADITOU, E.; PERISTERAKI, P.; CHARTOSIA, N.; SALMAN, A. (Mediterranean Marine Science, 2011)
The neon flying squid Ommastrephes bartramii is found circumglobally in subtropical, temperate waters and sustains important fisheries in the North Pacific, but it is rarely encountered in the Mediterranean Sea. During the last decade, and particularly since 2004, the frequency of its presence in the Aegean Sea and nearby regions has increased, raising a question about a change in the species distribution and abundance in this area. In this study, we reviewed the literature on O. bartramii findings in the Mediterranean Sea and present new data describing body and beak morphometry, diet and the maturity of specimens recently collected from the easternmost basins. According to data from the entire Mediterranean Sea, collected individuals reached 66 cm in mantle length (ML), wherein only females were larger than 32 cm in ML. An isometric growth in body weight (BW) was shown, whereas the lower beak rostral length (LRL) was allometrically positive in relation to the ML. Occasional catches by jigs during experimental cruises provided most of the individuals recorded in the period from 1982-1992. In contrast, the most recent records are primarily comprised of mature females collected on or near the shore in the eastern basin and of predominantly smaller individuals from the western basin caught by professional jigging fisheries. The distribution of the specimen recorded from the Aegean Sea indicates an association between the species distribution and the circulation of the warm Levantine Intermediate Water. The more frequent observations of moribund spawning females at the periphery of the Cretan Sea are indicative of a spawning ground at this area. The suspected recent increase of O. bartramii abundance in both the northeastern and northwestern basins might be due to the warming of upper sea layers, which has been observed since the mid-1980s and is considered to be the main factor driving the northward expansion of the warm-water species’ range within the Mediterranean Sea.